PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE TRADING PLACETERHADAP PEMAHAMAN KONSEP MATEMATIS SISWAKELAS VIII SMPN 1 LUBUK BASUNG TAHUN PELAJARAN 2013/2014 - Marisa, Marisa; Rismen, Sefna; Lovia, Lita (STKIP PGRI Sumbar, 2013)
The background of this research is student ability in offering opinion also less interaction and student comprehension of mathematical concept is low. This research purposed to know whether students comprehension of mathematical concept which used Active Learning Strategy TypesTrade Place better than using conventional Learning at eight grades of Junior High School number 1 LubukBasungacademic year 2013/2014. This research is an experimental research which random design of the subject. Population of this research is eight grades student of junior high school number 1 LubukBasungacademic year 2013/2014. Technique of random sampling was selected class VIII.2 as experiment class and class VIII.7 as control class. Instrument is comprehension test of mathematical concept in essay form with reliability of test is examines t one side with software MINITAB 14.Based on finding of examine hypothesis get p-value =0,002 it means lower than . so hypothesis in this research was accepted that students comprehension of mathematical concept which use Active Learning Strategy TypeTrading Places is better than student comprehension of mathematical concept which use conventional learning at eight grades of junior high school number 1 LubukBasung academic year 2013/2014.